ANALISIS OIL LOSSES PADA PROSES PENGOLAHAN MINYAK INTI KELAPA SAWIT DI PT. XYZ DENGAN METODE SEVEN TOOLS - Almira Ulimaz; Nuryati Nuryati; Yuliana Ningsih; Summa Nur Hidayah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2021)
One form of efficiency that can be done by palm oil mill companies so that production targets are achieved is to reduce the number of oil losses or loss of oil in the process of making their products, in this case, are CPO and PKO. This is because the lower the amount of oil losses, the higher the CPO and PKO that will be produced. This study aims to analyze oil losses in the processing of Palm Kernel Oil or PKO with the seven tools method. Data collection techniques in this study used case studies based on literature studies and field studies. Data were analyzed descriptively qualitatively. The conclusion of this research is the analysis of oil losses in the process of making palm kernel oil using check sheets and histograms, the data obtained shows high oil losses in the company PT. XYZ with an average of 8.92% for 4 months, so it is necessary to make improvements that at improving the quality of good palm kernel oil (PKO). Analysis of PKO oil losses at PT. XYZ is also performed using a cause-and-effect diagram. This aims to identify the causes of oil loss which include raw materials, human resources (HR), machinery, and the environment in order to fulfill the oil loss standard designed by the company, which is less than 8.00%, and also prevent high oil losses. which may happen again in the future.